A Randomized Double Blind Controlled Trial of Ringers Lactate Versus Normal Saline Among Pediatric Patients with Acute Severe Diarrhea - Bela Shaikh, Ifra, Saminanaz Ghoto, Aziz Ullah Langah, Syeda Amber Zaidi, Syed Fazal E Karim Faisal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare ringer’s lactate versus normal saline as a fluid replacement therapy among pediatric patients with acute severe diarrhea and dehydration. Study Setting: A quasi experimental study was undertaken at Paediatric medicine department, “Peoples university of medical and health sciences for women Nawabshah during April to September 2021”. Material and Methods: A quasi experimental study was conducted. Randomly participants were divided in two groups, in group A Ringer lactate was given while in group B normal saline was given for fluid replacement. Detailed history, clinical findings, demographic details and the serum electrolytes, renal parameters and acid-base status of participants of both groups were noted on a pre-formed proforma, before and after 6 hours of starting fluid replacement therapy. Data was analyzed by using SPSS V-20. Results:Mean age of the study participants of RL groups was 3.35 ± 1.22 and 3.39 ± 1.19 of NS group with male predominance. At the time of admission, there was no significant association of demographic and clinical characteristics between RL and NS groups.After starting treatment, at the end of 6 hours the status of dehydration and pH were improved more in the participants of RL group. The change in serum electrolytes comprising potassium, chloride and sodium were greater in groups RL, on the other hand, significant p-values were noted only with sodium and potassium. Looking over the acid-base status, the alteration in pH and serum bicarbonate was greater in group RL as compared to group NS with significant p-value. Conclusion:It can be concluded that the ringer’s lactate is superior to normal saline as a fluid replacement therapy in pediatric patients of acute gastroenteritis.